Get expert insights and community support for your questions on IDNLearn.com. Join our knowledgeable community to find the answers you need for any topic or issue.

solve for x -
[tex]x {}^{2} - 6x + 5= 0[/tex]


ty! ~​


Sagot :

Answer:

x = 5, x = 1

Step-by-step explanation:

Hello!

We can solve this quadratic by factoring.

Solve

  • [tex]x^2 - 6x + 5 = 0[/tex]
  • [tex]x^2 - 5x - x + 5 = 0[/tex]
  • [tex]x(x - 5) - 1(x - 5) = 0[/tex]
  • [tex](x - 5)(x - 1) = 0[/tex]

Use the zero product property:

  1. x - 5 = 0
    x = 5
  2. x - 1 = 0
    x = 1

x = 5, or x = 1